EFEKTIFITAS MODUL DAN AUDIO VISUAL TERHADAP PENGETAHUAN TENTANG DETEKSI KANKER SERVIKS MELALUI METODE IVA PADA WUS SUKU TERASING DI WILAYAH KERJA PUSKESMAS TAMILOUW KABUPATEN MALUKU TENGAH - Denicell Paulina Tetelepta; Rigoan Malawat; Joula Timisela (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2021)
Background: Cervical cancer is a type of cancer that 99.7% is caused by the oncogenic human papilloma virus (HPV), which attacks the cervix. The groups at risk for cervical cancer are women of childbearing age who engage in sexual activity at an early age, have many children and have poor reproductive health behavior. The habit of changing sexual partners is one of the main factors in transmitting the HPV virus. One of the "Pinamou" traditions, the isolated tribal community in the working area of ​​the Tamilouw Health Center provides opportunities for adolescents to engage in sexual activity at an early age, marry/marry at an early age, the average number of children is more than four, giving birth with complications/bleeding. Therefore, it is necessary IVA examination for early detection of cervical cancer. Objective: The purpose of the study was to determine the effectiveness of audio-visual modules and media on knowledge about cervical cancer detection through the IVA method in Wus from isolated tribes. Methode: The research method is a quantitative research using a quasi-experimental design through a pretest posttest one group design approach. The number of samples used were 66 respondents with consecutive sampling technique that met the inclusion and exclusion criteria consisting of 33 respondents using modules and 33 respondents using audiovisual. Data were collected using a questionnaire and then analyzed descriptively using the Wilcoxon rank test formula and the Mann-Whitney test. Result: The results showed that health education using modules and audiovisuals had an effect on WUS knowledge about early detection of cervical cancer in the Tamilouw Health Center Work Area, and the use of audiovisuals was more effective than modules in increasing WUS knowledge. The cooperation of cadres and village officials is needed to disseminate information and knowledge to be followed up on VIA examinations in Health Services. Keywords: Audio visual; IVA; Module; Knowledge; WUS